Cooperation, Clusters, and Knowledge Transfer Universities and Firms Towards Regional Competitiveness - Ferreira, Joô J.M.; Raposo, Mr̀io.; Rutten, Roel.; Varga, Attila. (Advances in Spatial Science, The Regional Science Series, 2013)
Cooperation and clusters have become the guiding paradigms for explaining and promoting regional competitiveness, but the cooperation process between firms and universities and the transfer of knowledge in guiding and nurturing regional competitiveness has received relatively little attention. This book strives to fill this gap in highlighting the connection between inter-firm cooperation in regional clusters, innovation and regional networks, and the role of universities in them . It goes beyond the traditional economic approach of clusters and includes <U+0018>soft factors<U+0019> in the explanation of regional competitiveness, and connects the literature on clusters to the literature of learning and knowledge creation as sources of regional competitiveness. It aims to foster an international and interdisciplinary exchange of perspectives by presenting current developments, case studies, best practices as well as new integrated theoretical approaches and applications.